TRANSFORMATIONAL LEADERSHIP IN THE INCLUSIVE EDUCATION - Azizah, Kuni; Sulistyorini (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2025)
This study aims to analyze the practice of transformational leadership by the school principal in managing inclusive education at SD Muhammadiyah 1 Tulungagung. Adopting a qualitative approach with a case study design, data were collected through observation, in-depth interviews, and documentation. The findings indicate that the school principal consistently demonstrates proactive, visionary, and highly transformational leadership. This is evident in their strategic decision-making, such as implementing SWOT analysis for program planning and fostering critical collaborations with external experts like the Autistic Service Center (PLA) Blitar. Furthermore, the principal's leadership is prominent in human resource management, including the appointment and continuous professional development of special accompanying teachers (GPK), and actively leading curriculum and assessment adaptations to cater to diverse student needs. The school employs flexible inclusive learning models, specifically regular classes with clusters and full special classes, adapted based on individual student requirements. While challenges such as managing tantrum behaviours in some students with special needs were identified, the principal demonstrated effective responses through dedicated GPK support, therapy recommendations, and robust collaboration with parents. This research concludes that transformational leadership is a pivotal factor in establishing and sustaining a high-quality, effective, and adaptive inclusive educational environment.